Dynamical analysis of a complex competitive two-strain epidemic network model with vaccination - A. Abdelkhalek; A.H. Abdel Kader; I.L. El-Kalla; A. Elsaid; Amr Elsonbaty; K.S. Nisar (Partial Differential Equations in Applied Mathematics)
Developing accurate models to replicate epidemic transmission poses a significant challenge for researchers both now and in the foreseeable future. Therefore, this work proposes a new complex competitive two-strain epidemic network model that incorporates vaccination. We derive the mathematical model, compute the disease-free equilibrium point, and determine its stability conditions. The basic reproduction number is computed to determine the epidemic threshold. The stability regions in parameter space and the effects of vaccination parameters are obtained. The conditions for transcritical bifurcation are established, and the parameter analysis for this type of bifurcation is conducted. Numerical simulations of various scenarios with varying parameter values validate the theoretical analysis.